2021
DOI: 10.1039/d0na01046d
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in two-dimensional materials for terahertz protection

Abstract: With the wide applications of Terahertz (THz) devices in future communication technology, the THz protection materials are essential to overcome potential threats. Recently, THz metamaterials (MMs) based on two-dimensional (2D)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…That is, the absorber is an excellent terahertz wave absorbing material, and an excellent shielding material mainly based on absorption, which can effectively avoid secondary pollution caused by reflection. [84,85] Hence, RGOFGT400 absorber is a high-performance EMA material in terahertz bands. Because of the limitation of resonance frequency, most natural magnetic materials (materials prepared by physical methods or synthesized by chemical methods) have no magnetic response in terahertz bands.…”
Section: Room Temperature Ferromagnetism and Multispectral Compatible...mentioning
confidence: 99%
“…That is, the absorber is an excellent terahertz wave absorbing material, and an excellent shielding material mainly based on absorption, which can effectively avoid secondary pollution caused by reflection. [84,85] Hence, RGOFGT400 absorber is a high-performance EMA material in terahertz bands. Because of the limitation of resonance frequency, most natural magnetic materials (materials prepared by physical methods or synthesized by chemical methods) have no magnetic response in terahertz bands.…”
Section: Room Temperature Ferromagnetism and Multispectral Compatible...mentioning
confidence: 99%
“…Here synthesized irregularly shaped nanosheets demonstrated broadband THz absorption which we find very useful for the construction of absorbers for future technologies like 6G communication. Presently metamaterials and 2D materials 57 are effectively used as broadband absorbers. Chen et al demonstrated a single-band THz metamaterial absorber with three layers of metallic rings, SiO 2 , and a VO 2 film, which caused absorption by the localized magnetic resonance.…”
Section: Terahertz Absorptionmentioning
confidence: 99%
“…THz absorption is closely related to frequency. Pan et al [37] found that the absorption curve of graphene foam in the frequency band of 0.1-1.6 THz showed a gradient upwards trend with an increasing frequency. In this study, the absorption curve of MWCNT aqueous dispersion also shows a gradient rising trend with the increase of frequency in the 0.1-0.6 THz band under the stimulation of MF, as shown in Figures 12 and 15.…”
Section: Thz Spectral Characteristics Of Mwcnt Aqueous Dispersion Und...mentioning
confidence: 99%